The University of Mary Wrestling Anaerobic Performance Test (UMWAPT) - A wrestling specific new protocol - Eichmann, B.; Kobes, J.; Sherve, C.; Aho, A.; Saghiv, M. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
BACKGROUND: The UMWAPT protocol simulates the anaerobic requirements of a full wrestling match, providing a way to measure the wrestler`s ability to complete an entire match against his most challenging opponent. PURPOSE: The purpose of the study was to compare and correlate the mechanical outcomes and fatigue index between the WAnT and the UMWAPT. METHODS: 15 wrestlers underwent both protocols in random order. Mechanical outputs (W), and fatigue index (%) were calculated and compared between the protocols and within the UMWAPT. RESULTS: Peak power correlations between protocols were weak to moderate, and weak to strong within the UMWAPT test. Mean power correlations between protocols were weak, and weak to strong within the UMWAPT test. Anaerobic capacity correlations between protocols were weak, and weak to strong within the UMWAPT test. Fatigue index correlations between protocols were weak, and weak to moderate within the UMWAPT test. Body weight relative peak power correlations between protocols were weak, and weak to very strong within the UMWAPT test. Body weight relative mean power correlations between protocols were weak, and weak to very strong within the UMWAPT test. All participants indicated the UMWAPT as a very accurate simulation of their most challenging wrestling match. CONCLUSIONS: The UMWAPT seems to be a very good protocol to simulate a wrestler`s most challenging match. The UMWAPT allowed the wrestlers to utilize their own technique, leading to better mechanical outputs, thus, it seems that this study gives hope that a wrestling specific all out performance protocol such as the UMWAPT be utilized, rather than a non-specific protocol such as the WAnT.